Dual prognostic significance of tumour-associated macrophages in human pancreatic adenocarcinoma treated or untreated with chemotherapy. Issue 10 (8th July 2015) - Di Caro, Giuseppe; Cortese, Nina; Castino, Giovanni Francesco; Grizzi, Fabio; Gavazzi, Francesca; Ridolfi, Cristina; Capretti, Giovanni; Mineri, Rossana; Todoric, Jelena; Zerbi, Alessandro; Allavena, Paola; Mantovani, Alberto; et al.
Abstract : Objective: Tumour-associated macrophages (TAMs) play key roles in tumour progression. Recent evidence suggests that TAMs critically modulate the efficacy of anticancer therapies, raising the prospect of their targeting in human cancer. Design: In a large retrospective cohort study involving 110 patients with pancreatic ductal adenocarcinoma (PDAC), we assessed the density of CD68-TAM immune reactive area (%IRA) at the tumour–stroma interface and addressed their prognostic relevance in relation to postsurgical adjuvant chemotherapy (CTX). In vitro, we dissected the synergism of CTX and TAMs. Results: In human PDAC, TAMs predominantly exhibited an immunoregulatory profile, characterised by expression of scavenger receptors (CD206, CD163) and production of interleukin 10 (IL-10). Surprisingly, while the density of TAMs associated to worse prognosis and distant metastasis, CTX restrained their protumour prognostic significance. High density of TAMs at the tumour–stroma interface positively dictated prognostic responsiveness to CTX independently of T-cell density. Accordingly, in vitro, gemcitabine-treated macrophages became tumoricidal, activating a cytotoxic gene expression programme, inhibiting their protumoural effect and switching to an antitumour phenotype. In patients with human PDAC, neoadjuvant CTX was associated to a decreased density of CD206 + and IL-10 + TAMs at the tumour–stroma interface. Conclusions: Overall, our data highlight TAMs as critical determinants of prognostic responsiveness to CTX and provide clinical and in vitro evidence that CTX overall directly re-educates TAMs to restrain tumour progression. These results suggest that the quantification of TAMs could be exploited to select patients more likely to respond to CTX and provide the basis for novel strategies aimed at re-educating macrophages in the context of CTX.